Endothelial cell loss associated with minimally invasive glaucoma surgery. Issue 2 (18th March 2022) - Seah, Ivan; Sng, Chelvin C.A.; Ang, Marcus
Abstract : Purpose of review: Minimally invasive glaucoma surgery (MIGS) represents a safer, albeit moderately effective surgical option for intraocular pressure control. However, the CyPass Micro-Stent (Alcon Laboratories) was withdrawn from the market in 2018 as the COMPASS-XT study demonstrated greater cornea endothelial cell (CEC) loss in patients who received the CyPass Micro-Stent with phacoemulsification compared with phacoemulsification alone. This led to the increased attention on MIGS-associated CEC loss and thus, this review will summarise the recent, available evidence on MIGS-associated CEC loss. Recent findings: Prospective clinical trials and retrospective observational studies published between 2011 and 2021 reported a wide range of 12 month CEC loss from 'insignificant', and up to 14.6%, for phacoemulsification combined with various MIGS procedures. Recent clinical trials over the same time period reported CEC loss of 12.8–15.2% associated with phacoemulsification alone. Summary: Apart from the CyPass Micro-Stent clinical trial, no other studies on combined phacoemulsification with MIGS that is 'phaco-plus' procedures have reported a higher short-term CEC loss compared with phacoemulsification alone. However, studies that specifically examine postprocedural CEC loss following phacoemulsification compared to 'phaco-plus' procedures over a longer follow-up period are required.